THE SHELF LIFE OF BROILER MEAT POST-RISED IN CLOSED HOUSE VIEWING FROM CHEMICAL-PHYSICAL QUALITY ASPECTS - M. A., Fathurrohman; Ariana, I N. T.; Miwada, I N. S. (Jurnal Peternakan Tropika; Vol 10 No 2 (2022): Vol. 10 No. 2 Tahun 2022; May - August, 2022)
This study aims to determine the chemical-physical quality of broiler meat after rearing in a closed house stored at room temperature. Completely Randomized Design (CRD) with a simple pattern with 4 treatments and 4 replications. The four treatments were M1 (1 hour shelf life); M2 (3 hours shelf life); M3 (5 hours shelf life) and M4 (7 hours shelf life) and each treatment was repeated 4 times. The breast meat, Musculus pectoralis superficialis was used as a sample in this study, derived from the slaughter of sixteen broiler chickens. The results showed that the increase in the shelf life of meat at room temperature did not affect the pH value (P>0.05), the pH value ranged from 6.10 - 6.19. Water holding capacity of meats ranged from 20,94% - 30,47% (P>0.05). Cooking loss of meats ranged from 28.92% - 32.55%, (P>0.05). Moisture content of meat was obtained in the range between 69.06% - 76.16%, (P>0.05). Protein content of meat was in the normal range between 20.97% - 21.59%, (P>0.05). The conclusion of this study is broiler meat after rearing in a closed house has a shelf life of 7 hours at room temperature, reviewed based on chemical-physical characteristics (pH value, water holding capacity, cooking loss, water content and protein content) has not changed chemical-physical quality of meats.   Keywords: chemical-physical quality, broiler meat (breast).